2012
DOI: 10.1177/1941874412458677
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Neuroimaging Studies and Neurological Consultation to Evaluate Dizzy Patients in the Emergency Department

Abstract: Background and Purpose: Dizziness is a frequent reason for neuroimaging and neurological consultation, but little is known about the utility of either practice. We sought to characterize the patterns and yield of neuroimaging and neurological consultation for dizziness in the emergency department (ED). Methods: We retrospectively identified consecutive adults presenting to an academic ED from 2007 to 2009, with a primary complaint of dizziness, vertigo, or imbalance. Neurologists reviewed medical records to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
4
14
0
2
Order By: Relevance
“…Analysing the incidence of clinically significant findings in this study, screening methods should be taken into account, considering that all of the patients were examined by residents of neurology or neurology specialist unlike in other studies where CT scan was required by emergency physicians, general practitioner, internal medicine specialists and other. Navi et al, [ 21 ] reported 7% of relevant abnormal head CT scans in the ER what is consistent with our results. Grossman et al, [ 22 ] reported 5% of abnormal head CT findings after excluding patients with trauma, altered mental status, seizure and hypoglycaemia what is also similar to our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Analysing the incidence of clinically significant findings in this study, screening methods should be taken into account, considering that all of the patients were examined by residents of neurology or neurology specialist unlike in other studies where CT scan was required by emergency physicians, general practitioner, internal medicine specialists and other. Navi et al, [ 21 ] reported 7% of relevant abnormal head CT scans in the ER what is consistent with our results. Grossman et al, [ 22 ] reported 5% of abnormal head CT findings after excluding patients with trauma, altered mental status, seizure and hypoglycaemia what is also similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Mitsunaga et al, [ 16 ] reported 18.6% admission to the hospital for the patients with vertigo. We also report an admission rate of 27.8% for patients with vertigo, which is similar to the 22% of patients admitted to the hospital from the ED in the study Navi et al, [ 21 ]. In our study patients with vertigo with positive clinically significant CT findings had higher admission rate which is consistent with study Mitsunaga et al, [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…Dizziness is one of the most common presenting complaints in emergency departments (EDs) [17,30]. Diagnosing patients with dizziness is challenging and ED physicians often request neurological consultation and brain imaging studies to differentiate non-vestibular medical causes (e.g., orthostatic dizziness) from peripheral (e.g., benign paroxysmal positional vertigo) or central vestibular disorders (e.g., brainstem/cerebellar stroke) [11,27]. The likelihood of detecting an acute brain lesion (ABL), for instance a stroke, inflammatory lesion or tumor, varies greatly depending on the clinical preselection process of patients and the modality and timing of brain imaging studies.…”
Section: Introductionmentioning
confidence: 99%
“…Most comparable series have utilized CT as the neuroimaging tool of choice 12,21 and not unexpectedly, reported low diagnostic yields, although a few studies have recently included MRI. 20,34 A study comparable to the present study 34 reported a diagnostic yield of MRI of 9.2%, although MRI was performed within 2 weeks of the patient being seen in the emergency department so a false-negative rate (due to reversal of DWI changes without T2/fast low-angle shot [FLAIR] changes on follow-up) 35 for stroke may have lowered the overall yield.…”
Section: Tablementioning
confidence: 69%